Influence of consumption values on housing furniture satisfaction among working women in Jeddah, Saudi Arabia - Makkawi, Fattwo Abdulrahman A (2022)
Furniture is an essential component of a room and different rooms have different types of furniture. People can judge the types of activities in the room by looking at the furniture available in the room. Its proper arrangement can make the small apartment a comfortable place to live in and can also assist women doing home activities more effectively and efficiently, especially among working women when they come back from work and continue to do home activities. This study aims to determine the influence of consumption values on housing furniture satisfaction among working women living in an apartment in Jeddah, Saudi Arabia. The theory of consumption values by Sheth et al. (1991a, 1991b) was adopted for this study. The five dimensions of this theory, i.e., functional value, emotional value, social value, epistemic value, and conditional value were tested on the working women's satisfaction with furniture in the three major rooms of the house, kitchen, living room, and bedroom. The multi-stage sampling was employed, as a sample of 350 Saudi working women was selected from three government sectors in Jeddah, such as general education, higher education, and health. A questionnaire was sent to the respondents through their respective e-mails, and normality and reliability tests were applied to test the validity and reliability of the data collected from the respondents. In addition, a multiple regression analysis was conducted in SPSS to test the correlation between consumption values and customer satisfaction. According to the results of multiple regression analysis, it was found that conditional value, functional value, and emotional value have a significant influence on working women’s satisfaction with furniture in the living room and kitchen. On the other hand, conditional value and emotional value were found to have a positive and significant impact on working women’s satisfaction with bedroom furniture. In general, conditional, functional, and emotional values had a significant positive effect on home furniture satisfaction among working women in Jeddah, Saudi Arabia. The results of the current study are valuable not only to working women but also to academic research, to better understand the existing habits and culture and to suggest and improve the quality of life of working women in Jeddah by finding new solutions that can lead to more satisfaction, less stress, and better work and family life balance.